Orientalist objective in al-Quran translation - Abuulaiqah, Yousif Mousa Ali Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2015)
The Traditional Orientalism has adopted a new approach, which is the translation of the Holy Quran. However, this does not mean that it had completely abandoned other approaches of traditional Orientalism namely; study of different Islamic sciences, study of the Holy Quran and Hadith, study of Islamic Jurisprudence, study of Islamic history and study of Arabic language and literature. But, the presence of this approach in the contemporary Orientalism is not new; rather it has adopted the same method of the traditional Orientalism. Undoubtedly, this approach has a great influence on the image of Islam in the West. As a result of this misconception, it has become necessary to conduct a research on the views of Orientalism about Islam, especially on the Holy Quran being the Holy Book of Muslims. The main focus of the study is to alert on the secretive resources of Orientalism which aim at fighting against Islam especially through translation of the Holy Quran. The question to be answered here is, was the translation of the Holy Quran by the Orientalist a call to embrace Islam? Or their main motive behind that was to distort the Holy Quran and to distance the Christians from it? Certainly, understanding the characteristics and strength of Islam lies on the translation of the Holy Quran. Thus, the translations were made in order to respond to those issues that are against Christianity in the Holy Quran. For this reason, this study is of paramount importance as it explains apparently the major target of Orientalism, i.e. the urgent need to understand the situation of Muslims; by translating the Quran into European languages by using great Orientalist in the Arab countries. This research has a number of objectives and most important amongst them are: responding to the misconception of the Orientalist and revealing their major motive behind translation of the Holy Quran into different European languages. The methodologies adopted in this research are: descriptive and historical approach to examine the text and documents and to classify and analyze them in order to find the relationship between them. According to the result of this research, it has been established that European churches have worked towards strengthening Christianity through allegations and distortions against Islam in order to keep Christians aloof from Islam.